2017
DOI: 10.3171/2016.4.jns16409
|View full text |Cite
|
Sign up to set email alerts
|

Associations of renin-angiotensin system genetic polymorphisms and clinical course after aneurysmal subarachnoid hemorrhage

Abstract: OBJECTIVE Renin-angiotensin system (RAS) genetic polymorphisms are thought to play a role in cerebral aneurysm formation and rupture. The Cerebral Aneurysm Renin Angiotensin System (CARAS) study prospectively evaluated associations of common RAS polymorphisms and clinical course after aneurysmal subarachnoid hemorrhage (aSAH). METHODS The CARAS study prospectively enrolled aSAH patients at 2 academic centers in the United States. A blood sample was obtained from all patients for genetic evaluation and measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Both the recessive AGTR2 A/C allele SNP (OR 4.70, 95% CI 1.43-15.4) and the recessive effect of the insertion allele of the ACE rs4340 insertion-deletion polymorphism (also known as rs4646994; OR 3.63, 95% CI 1.04-12.7) were linked to an increased risk of symptomatic cerebral vasospasm. 47 Similarly, another study demonstrated a link between impaired reactivity to CO2, measured using TCD ultrasonography, and the angiotensinogen (AGT) rs699 CC genotype (P=0.00028) in healthy elderly volunteers. 49 In addition, research in patients with TBI supports the link between ACE rs7221780 (OR 2.67, 95% CI: 1.25 -5.72) and rs8066276 (OR 3.82, 95% CI: 1.80 -8.13) and global patient outcome, with the minor alleles linked to a worse 6-month Glasgow Outcome Scale (GOS) score.…”
Section: [H1] Myogenic Mechanismsmentioning
confidence: 95%
See 1 more Smart Citation
“…Both the recessive AGTR2 A/C allele SNP (OR 4.70, 95% CI 1.43-15.4) and the recessive effect of the insertion allele of the ACE rs4340 insertion-deletion polymorphism (also known as rs4646994; OR 3.63, 95% CI 1.04-12.7) were linked to an increased risk of symptomatic cerebral vasospasm. 47 Similarly, another study demonstrated a link between impaired reactivity to CO2, measured using TCD ultrasonography, and the angiotensinogen (AGT) rs699 CC genotype (P=0.00028) in healthy elderly volunteers. 49 In addition, research in patients with TBI supports the link between ACE rs7221780 (OR 2.67, 95% CI: 1.25 -5.72) and rs8066276 (OR 3.82, 95% CI: 1.80 -8.13) and global patient outcome, with the minor alleles linked to a worse 6-month Glasgow Outcome Scale (GOS) score.…”
Section: [H1] Myogenic Mechanismsmentioning
confidence: 95%
“…Mutations in genes encoding angiotensin-converting enzyme (ACE) and the angiotensin II receptor have been linked to the development of delayed ischaemic neurological deficits in subarachnoid haemorrhage. 47,48 The type 2 angiotensin II receptor (AGTR2) A/C SNP (rs11091046) has been linked to the development of aneurysmal subarachnoid haemorrhage. Both the recessive AGTR2 A/C allele SNP (OR 4.70, 95% CI 1.43-15.4) and the recessive effect of the insertion allele of the ACE rs4340 insertion-deletion polymorphism (also known as rs4646994; OR 3.63, 95% CI 1.04-12.7) were linked to an increased risk of symptomatic cerebral vasospasm.…”
Section: [H1] Myogenic Mechanismsmentioning
confidence: 99%
“…Blood samples from all patients and controls enrolled in the Cerebral Aneurysm Renin Angiotensin System (CARAS) study were used for genetic evaluation; much of the method has previously been reported. [5][6][7]9,10 In the CARAS study, the diagnosis of aSAH was established on the basis of the admission CT scan or xanthochromia of CSF. A ruptured aneurysm as the source of hemorrhage was confirmed by CT angiography (CTA) or digital subtraction angiography (DSA).…”
Section: Methodsmentioning
confidence: 99%
“…In some laboratory studies, DCI improved after the administration of isoflurane as a result of the increase in eNOS expression [ 26 , 27 ]. The importance that NO plays in the effects of SAH has encouraged studies that seek to establish a relationship between the SNPs of eNOS , and the origin and complications of aSAHs [ 23 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Genetic Polymorphismsmentioning
confidence: 99%